Thermodynamic constraints on the formation of condensed carbon from serpentinization fluids. (15th September 2016) - Milesi, Vincent; McCollom, Thomas M.; Guyot, François
Abstract: Recent studies have identified carbonaceous material in serpentinite bodies, but whether these deposits have a biologic or abiotic origin remains uncertain. In this work, thermodynamic calculations were performed to examine the potential for abiotic condensed carbonaceous material to be produced from serpentinization-derived fluids under hydrothermal conditions. Calculation of reaction pathways during serpentinization of olivine showed that fluid compositions should equilibrate with condensed carbonaceous material, which controls the H2 and CO2 activities. Fluids from laboratory serpentinization experiments and from the Lost City and the Rainbow hydrothermal field are shown to be consistent with this model. The predictions indicate that carbonaceous material should be the dominant carbon product of CO2 reduction in these hydrothermal settings, which would have significant implications for a number of processes, including the deep Earth carbon cycle by creating a pool of relatively immobile reduced carbon, the extent of H2 production in ultrabasic environments, and mechanisms leading to abiotic reduced carbon compounds.